A non-isolated DC-DC buck-boost converter based on ZETA converter - Chua, Roy Kun Rui (Nanyang Technological University, 2021)
This report presents the implementations of the sliding mode and adaptive current mode controllers for the proposed ZETA converter [6]. This project aims to ensure that the mentioned controllers can control the proposed ZETA converter. The controllers must maintain the desired output voltage in the presence of load interference, change in desired voltage, and change in the proposed ZETA converter's input voltage. Various controller parameters are tuned to achieve a fast output voltage load transient response from initial to steady states. These tests' experimental results are present and evaluate to determine which controller is best in controlling the proposed ZETA converter.